Oxidation and sources of atmospheric NOx during winter in Beijing based on δ18O-δ15N space of particulate nitrate. (1st May 2021) - Zhang, Zhongyi; Guan, Hui; Xiao, Hongwei; Liang, Yue; Zheng, Nengjian; Luo, Li; Liu, Cheng; Fang, Xiaozhen; Xiao, Huayun
Abstract: The determination of both stable nitrogen (δ 15 N–NO3 - ) and stable oxygen (δ 18 O–NO3 - ) isotopic signatures of nitrate in PM2.5 has shown potential for an approach of assessing the sources and oxidation pathways of atmospheric NO x (NO+NO2 ). In the present study, daily PM2.5 samples were collected in the megacity of Beijing, China during the winter of 2017–2018, and this new approach was used to reveal the origin and oxidation pathways of atmospheric NO x . Specifically, the potential of field δ 15 N–NO3 - signatures for determining the NO x oxidation chemistry was explored. Positive correlations between δ 18 O–NO3 - and δ 15 N–NO3 - were observed (with R 2 between 0.51 and 0.66, p  < 0.01), and the underlying environmental significance was discussed. The results showed that the pathway-specific contributions to NO3 − formation were approximately 45.3% from the OH pathway, 46.5% from N2 O5 hydrolysis, and 8.2% from the NO3 +HC channel based on the δ 18 O-δ 15 N space of NO3 − . The overall nitrogen isotopic fractionation factor (εN) from NO x to NO3 − on a daily scale, under winter conditions, was approximately +16.1‰±1.8‰ (consistent with previous reports). Two independent approaches were used to simulate the daily and monthly ambient NO x mixtures (δ 15 N-NO x ), respectively. Results indicated that the monthly mean values of δ 15 N-NO x compared well based on the two approaches, with values of −5.5‰ ± 2.6‰,  −2.7‰ ± 1.9‰, and −3.2‰ ± 2.2‰ for November, December, and January (2017–2018), respectively. The uncertainty was in the order of 5%, 5‰ and 5.2‰ for the pathway-specific contributions, the εN, and δ 15 N-NO x, respectively. Results also indicated that vehicular exhaust was the key contributor to the wintertime atmospheric NO x in Beijing (2017–2018). Our advanced isotopic perspective will support the future assessment of the origin and oxidation of urban atmospheric NO x . Graphical abstract: Image 1 Highlights: Positive correlations between δ 18 O–NO3 - and δ 15 N–NO3 - were observed in PM2.5 during winter in Beijing. Contribution of daytime (45.3%) and nocturnal channels (54.7%) to NO3 − formation was comparable. The mean nitrogen isotopic fractionation factor from NO x to NO3 − in winter Beijing was +16.1‰ ±1.8‰. Vehicular exhaust dominated the wintertime NO x emissions in Beijing.